Activation of the NLRP3 Inflammasome Pathway by Uropathogenic Escherichia coli Is Virulence Factor-Dependent and Influences Colonization of Bladder Epithelial Cells - Demirel, Isak; Persson, Alexander; Brauner, Annelie; Särndahl, Eva; Kruse, Robert; Persson, Katarina (Frontiers in Cellular and Infection Microbiology, 2018)
The NLRP3 inflammasome and IL-1β release have recently been suggested to be important for the progression of urinary tract infection. However, much is still unknown regarding the interaction of UPEC and the NLRP3 inflammasome. The purpose of this study was to elucidate what virulence factors uropathogenic Escherichia coli (UPEC) use to modulate NLRP3 inflammasome activation and subsequent IL-1β release and the role of NLRP3 for UPEC colonization of bladder epithelial cells. The bladder epithelial cell line 5637, CRISPR/Cas9 generated NLRP3, caspase-1 and mesotrypsin deficient cell lines and transformed primary bladder epithelial cells (HBLAK) were stimulated with UPEC isolates and the non-pathogenic MG1655 strain. We found that the UPEC strain CFT073, but not MG1655, induced an increased caspase-1 activity and IL-1β release from bladder epithelial cells. The increase was shown to be mediated by α-hemolysin activation of the NLRP3 inflammasome in an NF-κB-independent manner. The effect of α-hemolysin on IL-1β release was biphasic, initially suppressive, later inductive. Furthermore, the phase-locked type-1-fimbrial ON variant of CFT073 inhibited caspase-1 activation and IL-1β release. In addition, the ability of CFT073 to adhere to and invade NLRP3 deficient cells was significantly reduced compare to wild-type cells. The reduced colonization of NLRP3-deficient cells was type-1 fimbriae dependent. In conclusion, we found that the NLRP3 inflammasome was important for type-1 fimbriae-dependent colonization of bladder epithelial cells and that both type-1 fimbriae and α-hemolysin can modulate the activity of the NLRP3 inflammasome.